ANALISIS KEBUTUHAN MEDIA SPELLING CARD GAME UNTUK MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS V SEKOLAH DASAR - Fitriani, Rizki Tania Fitriani; Uswatun Hasanah; Otib Satibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to analyze the needs for Vocabulary Spelling Card Game media to improve English vocabulary mastery and spelling ability of fifth-grade elementary school students. This research is a preliminary step of a Research and Development (R&D) study using the 4D model Thiagarajan et al. (1974), specifically focused on the Define stage. A descriptive quantitative approach was employed, with data collected through a Guttman scale questionnaire (Yes/No) consisting of 23 items distributed to 44 fifth-grade students of SDN Kebon Pala 12 Pagi. The questionnaire was developed based on five analytical dimensions of the Define stage: front-end analysis, learner analysis, concept analysis, task analysis, and specifying instructional objectives. Data were analyzed using descriptive statistics through percentage calculation. Results indicate that students experience significant difficulties in memorizing and writing English vocabulary, particularly in spelling. The majority of students show a high need for game-based, visually supported, and group-oriented learning media. These findings confirm the necessity of developing Vocabulary Spelling Card Game as a media that integrates image cards, letter cards, and a competitive game mechanism, targeting the vegetables theme for fifth-grade students.